Stimulation of acupoint ST-34 acutely improves gait performance in geriatric patients during rehabilitation: a randomized controlled trial - Hauer, Klaus; Wendt, Isabel; Schwenk, Michael; Rohr, Christina; Oster, Peter; Greten, Henry Johannes (Archives of physical medicine and rehabilitation, 2011)
Hauer K, Wendt I, Schwenk M, Rohr C, Oster P, Greten J. Stimulation of acupoint ST-34 acutely improves gait performance in geriatric patients during rehabilitation: a randomized controlled trial. - Objective - To determine whether a specific regimen of acupoint stimulation improved gait performance in geriatric patients. - Design - Multiple-blinded, randomized, controlled intervention trial. - Setting - Geriatric ward rehabilitation. - Participants - 60 geriatric patients during rehabilitation. - Interventions - Both groups received a 1-time acupoint stimulation according to randomization. Stimulation of a verum acupoint (verum treatment) according to principles of traditional Chinese medicine was compared with a technically identical needle application on a nonacupoint (control treatment) in the control group. - Main Outcome Measures - Descriptive parameters were documented by valid, established tests. Gait performance was objectively measured by an electronic walkway before needling and after needling. - Results - All gait parameters showed statistically significant improvement after verum treatment compared with control treatment (velocity, cadence, stride length, cycle time, step time, single support, double support: P values all <.05) except for the base of support (P=.163). Effect sizes achieved by 1-time stimulation of an acupoint were low and ranged from .08 to .24. No severe adverse clinical events related to the intervention occurred. - Conclusions - Study results showed that a 1-time administration of a specific acupoint stimulation regimen statistically significantly improved gait performance during geriatric ward rehabilitation. If sustainability of effects can be documented, acupuncture may prove to be an inexpensive intervention that may mildly improve motor performance in frail geriatric patients.